Relative diagnostic yield of tests for disseminated tuberculosis among inpatients living with HIV - Dr Phiona Namale; Prof Graeme Meintjes; Dr Charlotte Schutz; Dr Linda Boloko; Dr Kate Haigh; Dr Marcia Vermeulen; Dr Bianca Sossen; Dr Muzuko Bagula; Dr Alexis Maseko; Dr Yoliswa Msomi; Dr Scott Lee-Jones; Dr Conor Colquhoun; et al. (International Journal of Infectious Diseases)
Introduction: HIV-associated tuberculosis (TB) is frequently disseminated among hospitalised patients and associated with high mortality particularly if diagnosis is delayed. Hospitalised patients with HIV are often not able to produce sputum for TB diagnosis. There is limited evidence on the yield of disseminated TB tests (urine and blood) among these patients. We aimed to determine the diagnostic yield of urine Xpert Ultra (uXPU), blood Xpert Ultra (blXPU), urine Alere LAM (uLAM) and TB blood culture (TB BC) among inpatients with HIV-associated disseminated TB. We analysed concordance between rifampicin susceptibility results from uXPU and tests from other samples for participants whose uXPU results showed rifampicin resistance. Methods: This diagnostic yield study was a cross-sectional study nested within a Phase III randomised controlled trial evaluating novel treatment strategies for patients hospitalized with HIV-associated disseminated TB. Inpatients with HIV and clinical features suggesting TB underwent testing on admission for disseminated TB using uLAM, uXPU, blXPU and TB BC. All patients who tested positive for at least one of the above tests at screening were included in the diagnostic yield study. Results: 997 participants were screened and 429 had at least one disseminated TB test positive. Of these 429, 243 (56.6%) were female, median age was 35, median CD4 and HIVVL log10 were 40 cells/uL and 5.44 log10 copies/mL respectively. uXPU had the highest diagnostic yield of 81% (95% CI 77% – 85%) followed by uLAM 69% (95% CI 64% – 73%), blXPU 30% (95% CI 25% – 34%) and TB BC 23% (95% CI 19% – 27%). 223 (52%) participants had both uLAM and uXPU positive. 98% of participants had either a positive uXPU or uLAM or both. 18 (4%) of participants had rifampicin resistance on at least one uXPU specimen: 12 had rifampicin resistance demonstrated on uXPU plus at least one other sample, and 6 had rifampicin resistance only on uXPU (2 of these had at least one sample reported sensitive to rifampicin and 4 had other samples negative for cultures and XPU). Discussion: Urine assays had higher diagnostic yield than blood assays. uXPU had a higher diagnostic yield than uLAM, which has policy implications as uXPU is not commonly used or available. Both of these urine assays may miss a TB diagnosis but the yield is increased when both are performed. A major limitation of this study is that it is not a diagnostic accuracy study but a diagnostic yield study. Conclusion: Among patients hospitalised with HIV-associated disseminated TB, over 80% were diagnosed based on a positive uXPU. Both the uXPU and uLAM should be performed among inpatients with advanced HIV and presumed disseminated TB.Euler diagram showing intersection of numbers of patients positive per specified TB (Image) testhttps://drive.google.com/file/d/1dxXYFdWKI7VH1oYHCnKZtpldpTbcJw3s/view?usp=sharing